2022
DOI: 10.3389/fmed.2022.891863
|View full text |Cite
|
Sign up to set email alerts
|

Severe Disease in Patients With Recent-Onset Psoriatic Arthritis. Prediction Model Based on Machine Learning

Abstract: ObjectivesTo identify patient- and disease-related characteristics that make it possible to predict higher disease severity in recent-onset PsA.MethodsWe performed a multicenter observational prospective study (2-year follow-up, regular annual visits). The study population comprised patients aged ≥ 18 years who fulfilled the CASPAR criteria and less than 2 years since the onset of symptoms. Severe disease was defined at each visit as fulfillment of at least 1 of the following criteria: need for systemic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Besides, other studies built ML models based on blood immune profiling and serum proteomics to discriminate between PsA and psoriatic patients 106,107 . Based on these models, a minimal disease activity (a clinical state characterized by low levels of disease activity) predictive model was developed, with the variables of global pain, impact of the disease (PsAID), patient global assessment of disease, and physical function (HAQ‐Disability Index) having the greatest predictive ability 108 . Besides PsA, patient records were detected to identify the top predictors of noncalcified coronary plaque burden in psoriasis, which included obesity, dyslipidemia, and inflammation factors 109 .…”
Section: Ai Application In Psoriasis: Where We Are Nowmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, other studies built ML models based on blood immune profiling and serum proteomics to discriminate between PsA and psoriatic patients 106,107 . Based on these models, a minimal disease activity (a clinical state characterized by low levels of disease activity) predictive model was developed, with the variables of global pain, impact of the disease (PsAID), patient global assessment of disease, and physical function (HAQ‐Disability Index) having the greatest predictive ability 108 . Besides PsA, patient records were detected to identify the top predictors of noncalcified coronary plaque burden in psoriasis, which included obesity, dyslipidemia, and inflammation factors 109 .…”
Section: Ai Application In Psoriasis: Where We Are Nowmentioning
confidence: 99%
“…106,107 Based on these models, a minimal disease activity (a clinical state characterized by low levels of disease activity) predictive model was developed, with the variables of global pain, impact of the disease (PsAID), patient global assessment of disease, and physical function (HAQ-Disability Index) having the greatest predictive ability. 108 Besides PsA, patient records were detected to identify the top predictors of noncalcified coronary plaque burden in psoriasis, which included obesity, dyslipidemia, and inflammation factors. 109 Moreover, in a study conducted by Conic et al, the distribution width of red blood cells and mean platelet volume were examined as predictors of major cardiovascular events in persons with PsA, and the result indicated that parameter values above a certain threshold were associated with an increased cardiovascular risk and a poor therapeutic response.…”
Section: Preventive Medicinementioning
confidence: 99%
“…Таким образом, полученные нами данные частично согласуются с этими результатами. Следует отметить, что именно шкала «Боль» по PsAID-12 позволяет оценивать аспект, которому пациенты придают максимальное значение при описании своего состояния [16].…”
Section: в данном случае значение пмаб было значительно выше 389 что ...unclassified
“…However, due to the heterogeneity of this complex syndrome and despite the presence of well-known prognostic factors, there are still a few studies on the severity of disease course in PsA. The concept of severity has been often associated, or confused, with disease activity, but it has also been associated with the presence of polyarticular involvement, joint function reduction, and mainly damage [ 12 ]. Generally, the concept of severity should be distinguished from the mere inflammatory activity and, at present, this is still debated.…”
Section: Introductionmentioning
confidence: 99%